Light and Shadows in cardiac regeneration. - Giménez, Carlos Sebastián (2019)
Given that the adult human heart has an extremely limited regenerative capacity, diseases characterized by contractile cell loss, as myocardial infarction and cardiomyopathies, lead to ventricular remodeling and heart failure. Hence, diverse strategies to promote myocardial regeneration have been proposed and assessed in animals and humans with ischemic heart disease. Of these, gene transfer and especially stem cell therapy have been used. So far, the overall main outcome is a gross disparity between the promising results obtained in mammalian models and the poor, if any, benefit observed in randomized,controlled clinical trials. Many reasons may account for this disappointing scenario.Some, including flawed trial design and methodology, differences in cell type and dosing as well as in route of administration, erroneous end points selection and heterogeneous patient populations have been extensively discussed in comprehensive reviews. Others,more recently addressed, signal the use of inadequate or non-precise laboratorytechniques in cell identification and fate, this leading to precarious or misleadingconclusions. We hereby summarize part of the work done and quote some newapproaches, like the use of induced pluripotent stem cells and the promotion of selfregeneration by targeting the adult cardiomyocyte cell cycle, that may cast some light inthe otherwise shadowy field of cardiac regeneration.